Johannesburg as dystopia: South African science fiction as political criticism - Kirsten, Ashton Lauren (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2020)
This thesis will interrogate the spatial dynamics and configurations of one of the country's most prominent cities: Johannesburg. Johannesburg has been, and continues to be, a central focus in the nation's imaginary. There is a trend within South African science fiction (sf) "“ both literature and film "“ to portray Johannesburg as a dystopian, post-law, poverty-stricken space as a means of conceptualising the socioeconomic situation within the country. This study will isolate Johannesburg-based works of sf and interrogate why authors and filmmakers disproportionately return to this setting. Investigated are three contemporary works, namely, Zoo City (2010) by Lauren Beukes, Neill Blomkamp's film, Chappie (2015), and Dub Steps (2015) by Andrew Miller. This study explores the ways in which South African works of sf serve as social and political critique in the post-apartheid era of financial disparity, the formation of new boundaries, divisions of space and privilege, and the dereliction of critical infrastructure. The primary methodology of this thesis is that of Marxist literary analysis (specifically with reference to Louis Althusser's theoretical models), which will be conducted alongside discussions of authentic history of the country as well as political developments in order to illustrate how South African sf critically engages with, and succinctly critiques, its context. The aesthetics of African sf are inseparable from the politics of the past and the current moment and through the aesthetics of the future, South Africans can reimagine the politics of the now. This study therefore also revisits a selection of non-sf Johannesburg-set novels published post-1925 and argues that these texts can be studied as early examples of South African dystopian writing. In doing so, this study illustrates that dystopian writing about and in South Africa is not an advent of the 21st century, but an extension of a long history of critical engagement. This thesis suggests that the dystopian genre is helpful in reframing the issues of the present (and the past) so that some form of meaningful change is theorized. The underlying impulse of dystopian cultural production is ultimately hopeful: a worse context is imagined to warn society of its follies so that these shortcomings and issues can be corrected, thereby avoiding the disastrous world(s) portrayed in the fiction. In this way, this study contends that local sf should not be inextricably linked to the melancholia that thoughts of dystopia bring about. Rather, the nuanced criticism contained within these dystopian texts is testament to the country's ever-enduring spirit of change and transformation.
Keywords: Science fiction, South African -- History and criticism; Johannesburg (South Africa) -- Fiction; Science fiction films -- History and criticism; Dystopias in literature; Dystopian films; Politics in literature; Politics in motion pictures; Beukes, Lauren -- Zoo City; Blomkamp, Neill, 1979- -- Chappie; Miller, Andrew K., 1974 or 1975- -- Dub steps